2019
DOI: 10.1038/s41598-019-46144-5
|View full text |Cite
|
Sign up to set email alerts
|

A novel motif in the proximal C-terminus of Pannexin 1 regulates cell surface localization

Abstract: The Pannexin 1 (Panx1) ion and metabolite channel is expressed in a wide variety of cells where it regulates a number of cell behaviours including proliferation and differentiation. Panx1 is expressed on the cell surface as well as intracellular membranes. Previous work suggests that a region within the proximal Panx1 C-terminus (Panx1CT) regulates cell surface localization. Here we report the discovery of a putative leucine-rich repeat (LRR) motif in the proximal Panx1CT necessary for Panx1 cell surface expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…Until recently, it was held that Panx1 oligomerizes to form a homomeric hexameric channel (Penuela et al, 2013;Chiu et al, 2018). This conclusion was based on cross-linking studies (Boassa et al, 2007;Chiu et al, 2017;Epp et al, 2019) and EM with negative staining of the isolated protein (Wang et al, 2014;Chiu et al, 2017). Acceptance of these findings was facilitated because a hexameric oligomeric state of Panx1 matched that of connexin "hemichannels" (the half of gap junction channels in one of the two opposing plasma membranes).…”
Section: Activation Of Panx1 By Caspase Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…Until recently, it was held that Panx1 oligomerizes to form a homomeric hexameric channel (Penuela et al, 2013;Chiu et al, 2018). This conclusion was based on cross-linking studies (Boassa et al, 2007;Chiu et al, 2017;Epp et al, 2019) and EM with negative staining of the isolated protein (Wang et al, 2014;Chiu et al, 2017). Acceptance of these findings was facilitated because a hexameric oligomeric state of Panx1 matched that of connexin "hemichannels" (the half of gap junction channels in one of the two opposing plasma membranes).…”
Section: Activation Of Panx1 By Caspase Cleavagementioning
confidence: 99%
“…If the cross-linking agent is applied in very low concentrations and/or for an insufficiently long period, native interactions may not be captured fully, and using high concentrations for excessive periods of time can result in fortuitous linkages, resulting in overestimation of the oligomeric state. Interestingly, in one of the cross-linking studies on Panx1 ( Epp et al, 2019 ), monomeric Panx1 predominated, followed by intermediate oligomers (dimers and trimers), while the apparent hexameric form was barely detectable. In this setting, heptamers, even if present, would have escaped detection because of an insufficient amount of protein in that oligomeric state.…”
Section: What Is the Oligomeric State Of The Panx1 Channel?mentioning
confidence: 99%
“…26,27 Panx1 channels generally localize to the cell surface and intracellular membranes, and the trafficking process is dependent on protein glycosylation state and a leucine-rich region within the C-terminal region. 32,33 Panx1 are N-glycosylated at N254 in EL2, and this is the only identified glycosylation site (Figure 3). 18,33 Different types of glycosylation are observed in different tissues and subcellular locations, however, most Panx1 localized in the cell membrane exhibit complex glycosylation which may prevent gap junction formation.…”
Section: Pannexin-1 Structure and Functionmentioning
confidence: 99%
“…33,35 Notably, deletion of a leucine-rich region within the C-terminal domain decreases glycosylation and cell surface Panx1 expression, but the precise mechanism underlying the observed changes is not yet understood. 32 The C-terminal tail also appears to interact with actin microfilaments which facilitate the trafficking process and stabilize Panx1 at the plasma membrane. 3,36…”
Section: Pannexin-1 Structure and Functionmentioning
confidence: 99%
“…In addition, the presence of Panx1 in red blood cells, which lack mRNA, also suggests that Panx1 can remain active for an extended amount of time in the plasma membrane [ 47 ]. Delivery to the plasma membrane is an exquisitely regulated process for Panx1, mediated by motifs and/or post-translational modifications (see below) [ 48 , 49 ]. Once at the plasma membrane, strong evidence has demonstrated that extracellular ATP itself can induce internalization of the channel, providing an important negative feedback loop for Panx1 channel regulation [ 50 , 51 ].…”
Section: Pannexin 1 Structure Function and Post-translational Modificationsmentioning
confidence: 99%